Strategic planning for public and nonprofit organizations : a guide to strengthening and sustaining organizational achievement - Bryson, John M. (John Moore), 1947- (Business professional collection, 2018)
From identifying stakeholders and clarifying a shared vision, to implementing plans and revising strategies, this comprehensive, practical guide covers all aspects of the planning process to help you keep your organization united and on track into the future. --